2021
DOI: 10.3389/fnagi.2021.624731
|View full text |Cite
|
Sign up to set email alerts
|

Application of Functional Magnetic Resonance Imaging in the Diagnosis of Parkinson’s Disease: A Histogram Analysis

Abstract: This study aimed to investigate the value of amplitude of low-frequency fluctuation (ALFF)-based histogram analysis in the diagnosis of Parkinson’s disease (PD) and to investigate the regions of the most important discriminative features and their contribution to classification discrimination. Patients with PD (n = 59) and healthy controls (HCs; n = 41) were identified and divided into a primary set (80 cases, including 48 patients with PD and 32 HCs) and a validation set (20 cases, including 11 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…It is well known that the cerebellum affects motor and cognitive functions through the cerebellar-thalamic-cortical circuit ( Pierce and Péron, 2020 ). Studies have shown that multiple areas of the cerebellum in patients with PD are atrophied, the subthalamic nucleus has lost its ability to regulate connections in the cerebellum, and there are extensive cerebellar-cortical network abnormalities ( Shi et al, 2021 ). In patients with PD, the volume of cerebellar gray matter decreases, the connections within the cerebellum and between the cerebellum and the sensory-motor network increase, the connections between the cerebellum and the caudate nucleus, thalamus, and amygdala increase, and the connections between the auxiliary motor area and the cingulate gyrus decrease ( Tuovinen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the cerebellum affects motor and cognitive functions through the cerebellar-thalamic-cortical circuit ( Pierce and Péron, 2020 ). Studies have shown that multiple areas of the cerebellum in patients with PD are atrophied, the subthalamic nucleus has lost its ability to regulate connections in the cerebellum, and there are extensive cerebellar-cortical network abnormalities ( Shi et al, 2021 ). In patients with PD, the volume of cerebellar gray matter decreases, the connections within the cerebellum and between the cerebellum and the sensory-motor network increase, the connections between the cerebellum and the caudate nucleus, thalamus, and amygdala increase, and the connections between the auxiliary motor area and the cingulate gyrus decrease ( Tuovinen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…All subjects underwent structural and functional MRI scanning on a 3-T Siemens Verio scanner. Data acquisition parameters can be found in previous studies ( Hu et al, 2015 ; Shi et al, 2021b ). The structural images were acquired with high-resolution three-dimensional T1-weighted sequences [slices = 128, repetition time (TR)/echo time (TE) = 2,530/3.43 ms, field of view (FOV) = 256 × 256 mm, slice thickness/gap = 1.33/0.5 mm, matrix = 256 × 192, voxel size = 1 × 1.33 × 1.83 mm 3 , and flip angle (FA) = 7].…”
Section: Methodsmentioning
confidence: 99%
“…It can detect the amplitude of spontaneous, low-frequency oscillations of blood oxygen level-dependent signals to reflect the regularity and physiological state of neuron autonomous activity in different brain regions ( Qian et al, 2020 ). This approach provides a reliable and sensitive measurement to characterize the spontaneous neural activity and has been widely used in PD ( Cao et al, 2020 ; Tian et al, 2020 ; Pang et al, 2021 ; Shi et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the functional analyses, we selected left precentral, right precentral, left postcentral, and right postcentral from the Automated Anatomical Labeling (AAL) atlas ( 29) as the seeds because AAL is a commonly used atlas in functional space (30)(31)(32)(33)(34). We performed Pearson's correlation between each seed region and the whole brain voxel.…”
Section: Seed-based Functional Connectivity Analysesmentioning
confidence: 99%